The generic structures of the editorials of the Jakarta Post published in August 2020 - Ahmad Mubais (Concept : Community Concern for English Pedagogy and Teaching, 2021)
This study focuses on the analyze the generic structures and language features the editorials of the Jakarta Post to classify the type of exposition text and to know the appropriateness of being teaching material examples in studying a kind of text types. As the subject, six of editorials of the Jakarta Post published in August, 2020 were chosen randomly. The object is the generic structures of the editorials. Then, documentation is used as a technique of data collection to be analyzed and classified by using a book entitled “Text Types” by Mark and Kathryn, and a book entitled “English for Social Purpose” by Jenny Hammond to determine the appropriateness to be teaching material of genre. The results showed each editorial of the Jakarta Post consist of three generic structures, (1) thesis that introduces the topic, (2) series of arguments, (3) Summing up or recommendation as a conclusion that restate editorial writer’s point of view. Based on the features of the generic structures the two editorials belong to Hortatory Text and the rest belong to Analytic Text. All of the editorials also contain four features of a good argument, (1) clearly expressing point of view, (2) using reasons to support the argument, (3) using evidence to prove the argument, (4) showing cause and effect (conclusion) and appropriate to be teaching material. Keywords: Genres; generic structures; editorials; the Jakarta Post.